KAJIAN KESESUAIAN PENGGUNAAN LAHAN DENGAN RENCANA POLA RUANG DI KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR TAHUN 2022 - Fidya Ika Pangesti; Ahmad; Setya Nugraha (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2024)
Evaluation of land use with spatial patterns in the Regional Spatial Plan (RTRW) is very important to do, so that areas that are experiencing development can be sure that they are in accordance with the established spatial patterns. This study aims to analyze land use in Gondangrejo District in 2022, and analyze land use agreements with the Spatial Pattern Plan for Gondangrejo District, Karanganyar Regency in 2022. The analysis was carried out using a concurrent embedded method based on qualitative research. The results of this study are land use in Gondangrejo District, Karanganyar Regency in 2022, which dominates rice fields with a total area of 3,459.77 Ha. Land use suitability in Gondangrejo District with the highest suitable criteria, namely Dayu Village with an area of 622.79 Ha, areas that have land use suitability with the highest criteria not suitable, namely Plesungan Village with an area of 415.12 Ha, and the area that has the highest suitability for land use with unsuitable criteria, namely Jeruksawit Village with an area of 6.97 Ha.